Mesoscale developmental rivalry in the human extrastriate visual cortex - Shahin Nasr; Jan Skerswetat; Bryan Kennedy; Marianna E. Schmidt; Eric D. Gaier; Antony B. Morland; Peter Bex; David G. Hunter (Proceedings of the National Academy of Sciences, 2026)
The human extrastriate visual cortex contains fine-scale columns selectively responsive to motion, disparity, and color. However, the developmental interplay between these functional modules remains poorly understood. Using high-resolution functional MRI, we compared the mesoscale organization of the extrastriate cortex in 16 individuals with normal vision and 15 participants with amblyopia (PwA) caused by strabismus (n = 8) or anisometropia (n = 7). In controls, the cortical territory occupied by disparity-selective columns exhibited a competitive relationship with that of motion- and color-selective columns. In PwA, we witnessed a reduction in the size of disparity-selective columns accompanied by expansion of the cortical territory allocated to motion- and color-selective columns, while the interdigitated organization of these sites remained unchanged. At the macroscale, this phenomenon simply manifested as weaker disparity- plus stronger motion- and color-selective responses in PwA than controls. Our results show that the mesoscale modules are rivals in development allowing intact functions to usurp those that are compromised.